A metafictional reading of Massimo Bontempelli's La scacchiera davanti allo specchio - Giordano, Vita (Spunti e Ricerche, 2016)
By applying the notion of metafiction to La scacchiera and by illustrating examples taken from the work, it will be argued that La scacchiera deals with some of Bontempelli's initial views on the art of literary creativity.